Incarcerated in a Pandemic: How COVID-19 Exacerbated the “Pains of Imprisonment” - Craig, Miltonette Olivia (Criminal justice review, 2024)
Although the exact toll of COVID-19 in U.S. prisons and jails is relatively undetermined, estimates show that deaths due to the virus in the nation's correctional facilities are approximately six times higher than deaths in the general population. During the pandemic, jail and prison structures as well as significant overcrowding made it virtually impossible to institute protective measures against infection in correctional settings. Jail and prison administrators suspended in-person visitation, leaving those incarcerated even further isolated, and their friends and family in fear for the health and safety of their loved ones. The present study examines narratives of individuals who spoke about their experiences while incarcerated during the pandemic. The data for the study were gathered from prison reform advocacy organizations that featured individuals’ stories. The narrative findings provide insight into the traumatic experiences that incarcerated people endured, how institutional failures exacerbated their mistrust of the criminal legal system, and their efforts to cope.